Morphological, physiological, and transcriptional responses of the freshwater diatom Fragilaria crotonensis to elevated pH conditions - Zepernick, Brittany N.; Niknejad, David J.; Stark, Gwendolyn F.; Truchon, Alexander R.; Martin, Robbie M.; Rossignol, Karen L.; Paerl, Hans W.; Wilhelm, Steven W. (Frontiers in Microbiology, 2022)
Harmful algal blooms (HABs) caused by the toxin-producing cyanobacteria Microcystis spp., can increase water column pH. While the effect(s) of these basified conditions on the bloom formers are of a high research priority, how these pH shifts affect other biota remains understudied. Recently, it was shown these high pH levels decrease growth and Si deposition rates in the freshwater diatom Fragilaria crotonensis and natural Lake Erie diatom populations. However, the physiological mechanisms and transcriptional responses of diatoms associated with these observations remain to be documented. Here, we examined F. crotonensis with a set of morphological, physiological, and transcriptomic tools to identify cellular responses to high pH. We suggest 2 potential mechanisms that may contribute to morphological and physiological pH effects observed in F. crotonensis. Moreover, we identified a significant upregulation of mobile genetic elements in the F. crotonensis genome which appears to be an extreme transcriptional response to this abiotic stress to enhance cellular evolution rates– a process we have termed “genomic roulette”. We discuss the biological and biogeochemical effects high pH conditions impose on fresh waters and suggest a means by which freshwater diatoms such as F. crotonensis may evade high pH stress to survive in a “basified” future.